Meningkatkan Kinerja Pelayanan Surat Keterangan Tidak Mampu di Kantor Kecamatan Cikarang Timur Bekasi - Dede Wahyudin; Sungkono S (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The purpose of this study was to determine the performance of public services in the East Cikarang District Office, Bekasi Regency. This type of research was qualitative research, a certificate of incapacity at the East Cikarang District Office. Data collection techniques: observation, interviews and documentation. The results showed that the quality of service from the aspects of: 1. Tangible with indicators of employee appearance and convenience of places to perform services and the results of the interviews obtained that these dimensions had been well implemented, 2 Reliability with indicators of employee accuracy and employee capabilities and interview results obtained these has been implemented properly, 3 Responsiveness with indicators Responds to each service user and employee performs services quickly and the interview results obtained have been properly implemented 4. Assurance with indicators Officers provide timely guarantees and Officers provide guarantees of costs and interview results obtained this has been implemented properly 5. Empathy with the indicator Prioritizing the Interests of service users and Employees serves in a non-discriminatory manner and this has been implemented properly. Inhibiting factors there are still some from the public who complain and think that the performance of government is often lazy. Supporting factors include supporting factors so that employees can perform better services with the enthusiasm of each employee. And other supporting factors, namely the existence of facilities, namely computers and equipment as well as an internet connection from the Civil Registry which facilitates the service process for service users.